Sociology of the sacred : religion, embodiment and social change - Mellor, Philip A. (Sage Publications, 2014)
Drawing on classical and contemporary social theory, Sociology of the Sacred presents a bold and original account of how interactions between religious and secular forms of the sacred underpin major conflicts in the world today, and illuminate broader patterns of social and cultural change inherent to global modernity.--Provided by publisher